(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Speech is one of the most important tools for the full development of a person. An understanding of the surrounding people’s speech and the child’s active speech is essential in any pedagogical process. Language is an integral part of our lives. The language of science is one of the criteria of a certain level of science. Language is connected with thinking, and it is his weapon. Language lets you plan mental activities; in this process the task of managing the behavior of one’s tongue is the most important task of language. Language has appeared because people need communication. Linguistic sciences are widely used in psychology, medicine, engineering, aviation, space, judicial psychology, and so on. In this article, we aim to clarify the phenomenon of psycholinguistics on spelling activities, on the basis of which cognitive science fields, creative thinking, and creativity and their expression in speech, language, and thinking.